STAT5b: A master regulator of key biological pathways - Smith, Madison R.; Satter, Lisa R. Forbes; Vargas-Hernández, Alexander (Frontiers in Immunology, 2023)
The Signal Transducer and Activator of Transcription (STAT)-5 proteins are required in immune regulation and homeostasis and play a crucial role in the development and function of several hematopoietic cells. STAT5b activation is involved in the expression of genes that participate in cell development, proliferation, and survival. STAT5a and STAT5b are paralogs and only human mutations in STAT5B have been identified leading to immune dysregulation and hematopoietic malignant transformation. The inactivating STAT5B mutations cause impaired post-natal growth, recurrent infections and immune dysregulation, whereas gain of function somatic mutations cause dysregulated allergic inflammation. These mutations are rare, and they are associated with a wide spectrum of clinical manifestations which provide a disease model elucidating the biological mechanism of STAT5 by studying the consequences of perturbations in STAT5 activity. Further, the use of Jak inhibitors as therapy for a variety of autoimmune and malignant disorders has increased substantially heading relevant lessons for the consequences of Jak/STAT immunomodulation from the human model. This review summarizes the biology of the STAT5 proteins, human disease associate with molecular defects in STAT5b, and the connection between aberrant activation of STAT5b and the development of certain cancers.